Tradition of Forced-Marriage in Madura: a Perspective of Socio-Legal Feminism - Masthuriyah Sa'dan (Yayasan Jurnal Perempuan, 2015)
Forced-marriage is a Madurese tradition that forces daughters to marry to men being chosen by the parent. Usually they are betrothed while still in the womb or as a child. Average age of girls being married are under 18 years old. Even in some cases they were being wed on their 12-15 age. The preservation of the tradition can be found in certain areas in Madura such as Bangkalan, Sampang, Pamekasan and Sumenep. This tradition was formed because of customary law which merged with religious understanding of Madurese community about Islam, supported also by the economic conditions and low levels of education.